(untitled) (London Journal of Research In Management & Business, 2024)
The aim of our study is to identify and apprehend deeply the concept of civilization in Cameroon in order to determine the link in between civilization and human resource in Cameroon public Service. This will enable to understand how civilization and phenomena such as tribalism, nepotism, favouritism are linked. It will also be question to explore nepotismand favouritism as causes of ineffective system of accountability and ineffective HRM management in the Cameroon Customs. At the end of our scrutiny we shall formulate possible recommendationsconcerning the link between civilization and HRM in the CCA. Our study presents three main interest respectively an academic interest, a professional interest and finaly a socio-political interest. Our study falling in the domains of ethnography and mangement, three main methods were employed which areparticipant observation, interviews, and archival research in order to collect reliable data for our research. The study confirms that in specific sensitive public service such as customs, tribalismand hate speech seem to be rising and it kills competence. Corruption practices,nepotismandfavoritism, as well astribalism, have grown to levels previously unknown. It is therefore recommended among others to multiply and effectively implement recommandations from studies on Cameroonian culture with regards to political, administrative and socio economic impact; carry out an analysis of cultural identities in the CCA: this implies a chart on the ethnical representations in the said administration in order to identify demographic and strategic data for HRM policy and put in place a cultural HRM policy to efficiently use the various civilizational resources. Also, it would be relevant valueing the strenghts of different cultures to put in place mechanisms to tackle the identified weaknesses. The innovation here is that it proposes a cultural map and ethnical analysis of an organization in order to understand the strenghts and weaknesses of each culture so as to put it at the service of the general interest.